A beginner's guide to study extracellular vesicles in human blood plasma and serum - Rienk Nieuwland; Pia R‐M Siljander (Journal of Extracellular Vesicles, 2024)
Abstract Blood is the most commonly used body fluid for obtaining and studying extracellular vesicles (EVs). While blood is a standard choice for clinical analysis, using blood as a source of EVs introduces multiple layers of complexity. At the Blood Extracellular Vesicle Workshop organized by the International Society for Extracellular Vesicles in Helsinki (2022), it became evident that beginner researchers lack trustworthy information on how to initiate their research and avoid common pitfalls. This educational guide explains the composition and frequently used terminology of blood, provides guidelines for blood collection, and the preparation of plasma and serum. It also introduces the basic principles of isolating and detecting blood EVs while considering blood‐related factors. The goal of this guide is to assist beginners by offering a concise and evidence‐based introduction to the current knowledge and available resources to study blood EVs.